Crossbox Net Tool Model Development As a Volleyball Training Aid - Mangolo, Ewendi W; Islam, Rio Wakhid Hujjatul; Ramlan, Raphael (Jurnal Pendidikan Jasmani (JPJ), 2025)
Often the net comes loose and becomes loose, making it very disruptive to learning. Taking advantage of this phenomenon, researchers tried to develop a Crossbox training tool for volleyball. This tool has a very big function in learning and training. Able to adjust the height of the net without having to change the condition of the net permanently. This crossbox has a hook which is intended to hook the net so that tying the net to a permanent pole no longer happens. The tool developed by this researcher is also multifunctional. As the researchers wrote previously, this tool can also be used to support learning and practicing takraw, badminton and tennis. Therefore, researchers conducted research entitled the development of a crossbox net as a volleyball training tool. The researchers made the objectives of this research as follows: Know the crossbox net aids in learning volleyball, Find out the feasibility of the crossbox net tool product based on the validator's assessment. From the comparison test carried out, the aim was to find out whether the crossbox net training aid was effective in improving the user's service ability. The data obtained is based on the average of the pretest scores of 874. This is the score obtained before being given training aids. After the initial test was carried out, the tools were used with a training program created so that after being tested again, the service capability obtained a post-test score of 1303. By looking at these results, it can be concluded that there has been an increase in quantity.